2018
DOI: 10.1111/chso.12270
|View full text |Cite
|
Sign up to set email alerts
|

‘Out of Place around Other People’: Experiences of Young People Who Live with Food Insecurity

Abstract: We used a hermeneutic phenomenological approach to address the question, 'What does it mean to experience food insecurity?' Youth focus group interviews incorporating art/writing prompts and interviews with programme director interviews contributed to our understanding of youth feeling out of place around other people. Young people living in food-insecure homes in rural areas may experience complicated sets of interactions that simultaneously connect them to others living in similar circumstances, yet isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Research has also identified how food insecurity can impact on different populations. For example, research has highlighted the growing numbers of children in the UK who are experiencing food insecurity (Knight et al , 2018; Lambie‐Mumford and Sims, 2018; Lambie-Mumford and Green, 2017; Mott et al , 2018; Wills et al , 2018). Moreover research has shown how family members sometimes skip meals in order to ensure their children have enough to eat (Purdam et al , 2015; Tarasuk et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also identified how food insecurity can impact on different populations. For example, research has highlighted the growing numbers of children in the UK who are experiencing food insecurity (Knight et al , 2018; Lambie‐Mumford and Sims, 2018; Lambie-Mumford and Green, 2017; Mott et al , 2018; Wills et al , 2018). Moreover research has shown how family members sometimes skip meals in order to ensure their children have enough to eat (Purdam et al , 2015; Tarasuk et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of transition for young people with complex support needs are frequently far from normative. These young people must often navigate a plethora of multi-faceted transitions which can include experiences of violence (Lamb, Humphreys, & Hegarty, 2018); rejection and exclusion from formal education and other services (Paget et al, 2018); criminalization at an early age and frequent contact with police (Ellem & Richards, 2018); the loss of essential resources such as housing and/or income (Couch, 2017;Mott, Keller, Britt-Rankin, & Ball, 2018); and breakdowns in informal supports such as removal from families of origin, continual relocations resulting in instability and the loss of supportive relationships (Jakobsen & Christiansen, 2011;Atwool, 2016).…”
mentioning
confidence: 99%
“… 9 Those who experience food insecurity may feel simultaneously connected with others who are in a similar situation and also alienated from the rest of the community. 59 …”
Section: Discussionmentioning
confidence: 99%
“…Adults were the focus of this review, and though young people have less autonomy over food acquisition and choice, they still adjust to cope with food insecurity when their household does not have enough. In their study of youth in focus groups (n = 46), Mott et al 59 found that youth understood and expressed how factors in their environment influenced their food insecurity status, with themes such as limited employment opportunities for their parents and a lack of community connections. There is a demonstrated need for more research on the perspectives of children and youth; the potential physical consequences of nutrient deficiency during a time of rapid physiological development are great, and although adults tend to make sacrifices to account for this, they should not have to.…”
Section: Discussionmentioning
confidence: 99%